Digital libraries and crowdsourcing - Andro, Mathieu (London, UK : ISTE, Ltd. ; Hoboken, NJ : John Wiley & Sons, Inc., 2018)
Instead of outsourcing tasks to providers using labor-intensive countries, libraries around the world increasingly appeal to the crowds of Internet users, making their relationship with users more collaborative . These internet users can be volunteers or paid, work consciously, unconsciously or in the form of games. They can provide the workforce, skills, knowledge or financial resources that libraries need in order to achieve unimaginable goals.
A Conceptual Introduction to the Concept of Crowdsourcing in Libraries: A New Paradigm? -- Overview of Several Crowdsourcing Projects Applied to the Digitization of Libraries -- Overview and Keys to Success -- Conclusion.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed January 26, 2018).
Keywords: Digital libraries; Human computation; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Digital libraries; Human computation; Electronic books